Improving Employees Accountability and Firm Performance through Management Accounting Practices - Nik Mohd Norfadzilah, Nik Mohd Rashid; Nor Azlina, AbRahman; Normah, Omar; Aliza, Ramli (2016)
Evolution in the business environment will play a key role in spurring the growth of Small Medium Enterprises (SMEs) globally. Growing changes in business competition, daily operation, new strategy and technology are driving transformation in employees productivity and the future business environment that have significant impacts to organizations. Many organizations are demanding for proactive entrepreneurs with a dynamic team, who can run and steer their businesses to becoming more cost-efficient, which may lead to increased efficiency of firm performance. Literatures in management accounting recognize the important role of Management Accounting Practices (MAP) in Small Medium Enterprises (SMEs). This study examines the relationships between budgetary participation, commitment and performance measures through the tools and techniques of MAP in firm performance. A case study approach with heavy reliance on semi-structured interview was used, where 16 informants who are key decision makers and officer from different management levels were interviewed in the case study. Other sources of evidence have also been sought to enhance the desirability of the findings discussed. Our findings revealed that usefulness of MAP in the company improved employees’ accountability and firm performance. It also showed that budgetary participation and commitment from employees’ accountability have improvement activity when using MAP. This is directed towards helping others in achieving the desired business results by strategically positioning themselves into MAP in making informed decisions in their business undertaking. Further, the budgetary participation and commitment are predictors of managerial performance and accountability in perceived usefulness of MAP of firm performance outcomes.